Factors leading to inflation targeting: The impact of adoption - Anna Samarina; Jan-Egbert Sturm (ETH Zurich, KOF Swiss Economic Institute, 2013)
This paper examines how the analysis of inflation targeting (IT) adoption is affected by allowing for a structural change after adoption, using panel probit models for 60 countries over the period 1985-2008. Our findings suggest that there is a structural change after IT adoption. Including the post-adoption period when estimating the factors of IT adoption leads to biased results when interested in the question as of what drives countries' decision to adopt IT.
Keywords: E42; E52; 330; inflation targeting; panel probit